IMPROVING STUDENTS’ READING COMPREHENSION IN RECOUNT TEXT THROUGH KWL STRATEGY OF VIII GRADE AT SMP N 8 TOLITOLI - Mohammad Rafi'i (Universitas Madako Tolitoli, 2018)
The objective of this research is to find out whether kwl strategy can improve students’ reading comprehension or not.. This research is pre experimental research design consist of one group pre-test and post-test. The Population of this research is the eighth grade of SMPN 8 Tolitoli in 2016/2017 academic year. The sample of this research is selected by using purposive sampling technique and the selected class is VIIib consisted of 17 students. In collecting the data, the researcher took from the result of pre-test and post-test. The researcher analized the data statically.The result of the test showed that the students’ mean score in posttest 84.35is higher than pretest 61,18. To know the significant difference between pretest and posttest, the researcher compared the value of t-counted and t-table by applying 0.05 level of significance for two-tailed test with 16 degree of freedom (17-1=16), the researcher found that the tcounted (13,24) is higher than ttable (2,120) and the hypothesis of this research is accepted.The researcher concluded that applicationkwl strategy can improve students’ reading comprehension in recount text of eight grade at SMP N 8 Tolitoli. Key words:improving reading comprehension, and kwl strategy.